Sustentabilidade e habitação de interesse social na cidade de São Paulo: análise de obras - Veras, Mariana Ribeiro (2014)
This work aims to analyze the social interests habitations linked to the Urbanizations Slums Programs promoted by São Paulo city hall. Because of this project, two housing complexes were chosen, such as Mata Virgem residential and Parque Santo Amaro V residential. The methodological approach used parameters established by the Selo Casa Azul da Caixa Econômica Federal , which it has the purpose to stimulate the sustainable practices in the housing construction scope, promoting the enterprise certification. This evaluation covers questions like: urban quality, project and comfort; energy efficiency; the conservation of material resources; water management; social practices and accessibility. The results of this research show suggestions that expose quality architecture and improvements at the analyzed work, however according to the sustainable approach those enterprises express better incomes than the exposed before